2017
DOI: 10.25220/wnj.v01i1.0008
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between Serum Zinc Level and Erythrocyte Superoxide Dismutase (SOD) Activity in Non-frail and Frail Geriatric Patients

Abstract: Introduction: Frailty syndrome (FS), as a health problem in elderly, can interfere with the quality of life. Many factors play roles in its occurrence, one of which is oxidative stress. Superoxide dismutase (SOD), in which one of its components is zinc (Zn), is one of the endogenous antioxidants that plays a role in preventing oxidative stress. This study was aimed to know the correlation between serum zinc level (sZn) and erythrocyte SOD (eSOD) activity in non-frail and frail geriatric patients.Methods: This … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…No statistically significant differences were determined according to the nutritional status for the abovementioned enzymes in the presented study. Similarly, in the study by Pinontoan et al [ 50 ], no statistically significant differences were found for the erythrocyte SOD activity in non-frail and frail geriatric patients. The literature on the subject indicates an increase in oxidative stress markers (e.g., MDA) and a decrease in the activity of antioxidant enzymes (e.g., SOD and CAT) with the aging of the human body [ 9 , 51 ].…”
Section: Discussionmentioning
confidence: 63%
“…No statistically significant differences were determined according to the nutritional status for the abovementioned enzymes in the presented study. Similarly, in the study by Pinontoan et al [ 50 ], no statistically significant differences were found for the erythrocyte SOD activity in non-frail and frail geriatric patients. The literature on the subject indicates an increase in oxidative stress markers (e.g., MDA) and a decrease in the activity of antioxidant enzymes (e.g., SOD and CAT) with the aging of the human body [ 9 , 51 ].…”
Section: Discussionmentioning
confidence: 63%